Introduction : génétique et théâtre - Françoise Simonet-Tenant (Continents manuscrits)
After having reminded the key stages of genetic criticism development, Françoise Simonet-Tenant, resumes specific features of theatrical genesis. Indeed, the text and the performance are often tightly linked one to another. Thus, there are more and more protagonists in piece’s conception which is never limited to the "author" ; and the piece’s preparation chronology reveals difficult to map out. In fact, it seems always transient, in a constant renewal of following performances.